Utilizing Songs as a Medium for Teaching English Idioms: Bridging Linguistic Competence and Cultural Understanding in Indonesian EFL Students - Rafly, Muhammad; Nurcholis, Ivan Achmad (Yayasan Pendidikan Genlita Indonesia, 2025)
This study aims to analyze the use of idioms in songs as a means to understand their contribution to meaning, mood, and theme, while exploring their emotional, cultural, and narrative dimensions. Utilizing a qualitative research approach with a literature study design, the research collects data from relevant journal articles, books, and other academic sources, focusing on English as a Foreign Language (EFL) learning among Indonesian students. The instrument used is songs containing idioms, which serve as teaching tools to enhance students' understanding of idiomatic expressions. The findings indicate that although idioms are often overlooked in language instruction, the use of songs as a teaching medium proves effective in improving students' listening skills and memory of idioms. Songs not only provide an engaging and memorable context but also enrich students' cultural understanding. In conclusion, integrating songs into idiom instruction can enhance students' linguistic competence and cultural appreciation, making it an effective strategy for EFL educators to bridge the gap between language learning and cultural appreciation.